Microbial production of potent phenolic-antioxidants through solid state fermentation - Martins, S. (2010)
The agroindustrial residues including plant tissues rich in polyphenols were explored for microbial production of potent phenolics under solid state fermentation processes. The fungal strains capable of hydrolyzing tannin-rich materials were isolated from Mexican semidesert zones. These microorganisms have been employed to release potent phenolic antioxidants during the solid state fermentation of different materials (pomegranate peels, pecan nut shells, creosote bush and tar bush). This chapter includes the critical parameters for antioxidants production from selective microbes. Technical aspects of the microbial fermentation of antioxidants have also been discussed.